Untersuchung von Spulensystemen zur induktiven Energieübertragung von Elektrofahrzeugen. Vergleich von Topologien und Entwicklung einer Auslegungsmethodik - Knaisch, Katharina (Karlsruher Schriftenreihe Fahrzeugsystemtechnik / Institut für Fahrzeugsystemtechnik, 2017)
Wireless inductive charging improves user acceptance of electric vehicles, as it allows for a comfortable charging process. A mature inductive power transfer solution has to fulfill various requirements. In order to meet the various demands, at first, an appropriate structure of the magnetic coupler system has to be selected according to the specific case of application Afterwards, a comprehensive design methodology allows a fast and efficient dimensioning of the particular coil topology.